Improved function and proliferation of adult human beta cells engrafted in diabetic immunodeficient NOD-scid IL2rγnull mice treated with alogliptin - Jurczyk A (Dove Medical Press, 2013)
Agata Jurczyk,1 Philip diIorio,1 Dean Brostowin,1 Linda Leehy,1 Chaoxing Yang,1 Fumihiko Urano,2 David M Harlan,3 Leonard D Shultz,4 Dale L Greiner,1 Rita Bortell1 1Program in Molecular Medicine, University of Massachusetts Medical School, Worcester, MA, 2Department of Medicine, Washington University School of Medicine, St Louis, MO, 3Department of Medicine, University of Massachusetts Medical School, Worcester, MA, 4The Jackson Laboratory, Bar Harbor, ME, USA Purpose: Dipeptidyl-peptidase-4 (DPP-4) inhibitors are known to increase insulin secretion and beta cell proliferation in rodents. To investigate the effects on human beta cells in vivo, we utilize immunodeficient mice transplanted with human islets. The study goal was to determine the efficacy of alogliptin, a DPP-4 inhibitor, to enhance human beta cell function and proliferation in an in vivo context using diabetic immunodeficient mice engrafted with human pancreatic islets. Methods: Streptozotocin-induced diabetic NOD-scid IL2rγnull (NSG) mice were transplanted with adult human islets in three separate trials. Transplanted mice were treated daily by gavage with alogliptin (30 mg/kg/day) or vehicle control. Islet graft function was compared using glucose tolerance tests and non-fasting plasma levels of human insulin and C-peptide; beta cell proliferation was determined by bromodeoxyuridine (BrdU) incorporation. Results: Glucose tolerance tests were significantly improved by alogliptin treatment for mice transplanted with islets from two of the three human islet donors. Islet-engrafted mice treated with alogliptin also had significantly higher plasma levels of human insulin and C-peptide compared to vehicle controls. The percentage of insulin+BrdU+ cells in human islet grafts from alogliptin-treated mice was approximately 10-fold more than from vehicle control mice, consistent with a significant increase in human beta cell proliferation. Conclusion: Human islet-engrafted immunodeficient mice treated with alogliptin show improved human insulin secretion and beta cell proliferation compared to control mice engrafted with the same donor islets. Immunodeficient mice transplanted with human islets provide a useful model to interrogate potential therapies to improve human islet function and survival in vivo. Keywords: human islet transplant, DPP-4 inhibitor, glucose tolerance, plasma insulin